Effectiveness of MyKidEye in improving parents’ knowledge, attitude, and practice on children eye health care - Nor Diyana Hani Ghani; Norliza Mohamad Fadzil; Zainora Mohammed; Mohd Harimi Abd Rahman; Rosilah Hassan; Hanif Farhan Mohd Rasdi (PLoS ONE, 2026)
Background Vision problem among children is the most common health concern worldwide. Parental involvement plays an important role in addressing these issues especially through their Knowledge, Attitude, and Practice (KAP) regarding vision care. MyKidEye is an innovative smartphone application that contain information on common vision problem in children, early signs and symptoms, and treatment options to enhance parent’s KAP. This study aims to assess the effectiveness of MyKidEye application in improving parental KAP related to children’s eye health care. Methods This is a quasi-experimental study conducted from January to February 2023. The MyKidEye smartphone application was developed, and efficacy testing was performed. Parents from two schools who met the study criteria were selected and divided into two groups: the control group and the study group. Both groups completed the Parental Knowledge, Attitude, and Practice in Eye Problem among Children Questionnaire (PEPC-KAPQ) and their responses were recorded as pre-intervention data. Parents in the study group were given the MyKidEye application to be used for 4 weeks. Following a four weeks period, the PEPC-KAPQ was re-administered to both groups, and their responses were recorded as post-intervention data. Result A total of 178 parents were enrolled in this study, with 89 parents in the control group and 89 in the study group. Statistical analysis was performed using two-way mixed ANOVA to evaluate changes in parental knowledge, attitude, and practice score between groups over time. The practice scores of parents in the study group showed significant improvement after using MyKidEye, compared to the control group (F (1,176) = 34.27, p < 0.01). However, no significant changes were observed in knowledge (F (1,176) = 0.02, p = 0.88) or attitude score (F (1,176) = 2.82, p = 0.10). Conclusion MyKidEye application effectively improved parental practices related to children’s eye health care. It can serve as a valuable tool for improving and sustaining parents’ knowledge, attitudes, and practices regarding children’s eye health over a prolonged period, ultimately promoting better long-term eye care and awareness.